Pelacakan Secara Imunohistokimiawi Antigen Virus pada Ayam yang Diinfeksi dengan Virus Penyakit Tetelo (IMMUNOHISTOCHEMICAL DETECTION OF VIRAL ANTIGEN IN TISSUE OF CHICKENS EXPERIMENTALLY INFECTED WITH NEWCASTLE DISEASE VIRUS) - Mirah Adi, Anak Agung Ayu; Kardena, I Made; Astawa, Nyoman Mantik; Matsumoto, Yasunobu (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
In order to study the distribution of Newcastle disease virus (NDV) following infection, chickenswere experimentally infected with visceretropic velogenic NDV isolate. Monoclonal antibodies (mAbs)against the NDV LaSota vaccine strain were then produced to detect viral antigen in the infectedorgans. The mAbs were firstly tested for their specificity by enzyme linked immunosorbent assay(ELISA) using NDV and normal allantoic fluids as antigens. Eight mAbs specific against NDVwere isolated and two mAbs were used for immunodetection of NDV antigen in chicken’s tissues.By immunohistochemistry labeled streptavidin-biotin (LSAB) staining NDV–antigen was detectedin paraffin embedded tissues of NDV-infected chickens. NDV antigen was not detected in noninfected chickens. In the infected chickens, high intensity of NDV antigen was detected in thelymphoid tissues, lung and intestine. The NDV antigen with a lesser intensity was detected in thebrain, trachea, liver and myocardium. This study shows that although viscerotropic velogenicNDV isolate can infect almost all organs, the main target of infection are lung, intestine andlymphoids tissues
Keywords: Newcastle disease, LaSota, monoclonal antibodies, streptavidin biotin